Critical perspectives on plurilingualism in deaf education - Snoddon, Kristin; Weber, Joanne, 1959- (Multilingual Matters, 2021)
"This book is the first edited international volume focused on critical perspectives on plurilingualism in deaf education, which encompasses education in and out of schools and across the lifespan. It explores issues such as bimodal bilingualism, translanguaging, teacher education, sign language interpreting and parent sign language learning"-- Provided by publisher.
Keywords: Deaf people -- Education.; Multilingualism.; Multilingual communication.; Multilingual education.; Deafness; Education; Multilingualism; Personnes sourdes -- Éducation.; Multilinguisme.; Communication multilingue.; Enseignement multilingue.; LANGUAGE ARTS & DISCIPLINES / Sign Language.; Deaf -- Education; Multilingual communication; Multilingual education